Forensic Investigation Framework on Server Side of Private Cloud Computing - Sudyana, Didik; Lizarti, Nora; Erlin, Erlin (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 10, No. 3 December 2019, 2019)
Cloud Computing is one of the technologies that continue to develop and progress in rapid adoption rates due to the various benefits and conveniences offered. Cloud Computing has four types of adoption models, one of which is a Private model and is widely adopted by users because it is safer and customizable. The high level of cloud computing adoption is an opportunity for criminals to use cloud computing in committing their crimes and requires handling digital forensics. However, each cloud model has different characteristics, so the investigative method used is also different. Then there is no specific guidance for investigating cloud computing. So it is necessary to analyse the investigation of private cloud computing that used OwnCloud from the server-side and develop the novel investigation framework based on SNI 27037: 2014. An analysis of investigations is performed to develop the novel investigation framework and to find out what evidence can be found based on the novel framework. The results of the research conducted can be a reference for investigators to conduct forensic investigations in cloud computing on the server-side and the novel investigation framework will become a reference to be used as a guide to the investigation on private cloud computing in the server-side.